Wave-Induced Pressure Distribution on Placed Perforated Revetment Block. (2017) - Permana, Muhammad Sidik; Triatmodjo, Bambang; Yuwono, Nur
Abstract: In order to evaluate the stability of revetment block against wave attack, the information about hydrostatic pressure distribution induced by the wave is needed. In this paper, a simple mathematical model is developed to calculate the pressure distribution on revetment, which taking the effect of flow in filter layer and the perforated surface of revetment block into account. Physical test were done to observe the flow in filter and the coefficient discharge of perforated surface. The effect of filter and perforated surface latter on will called as filter-pore parameter. Model investigation were also performed on various filter under the loading condition which represent the wave loading. The result of this model investigation were compared to the mathematical model, and shows a great agreement between both of them. The result from both simulation shows that the filter-pore parameter has a great influence on the hydrostatic-pressure that act on the revetment block.